Curcurnin abrogates LPS-induced pro-inflammatory cytokines in RAW 264.7 macrophages. Evidence for novel mechanisms involving SOCS-1,-3 and p38 MAPK - Guimaraes, Morgana Rodrigues [UNESP]; Manzoli Leite, Fabio Renato [UNESP]; Spolidório, Luis Carlos [UNESP]; Kirkwood, Keith Lough; Rossa, Carlos [UNESP] (Elsevier B.V., 2013)
Curcumin is the active compound in the extract of Curcuma longa rhizomes with anti-inflammatory properties mediated by inhibition of intracellular signalling. SOCS and MAP-Kinases are involved in the signalling events controlling the expression of IL-6, TNF-alpha and PGE(2), which have important roles on chronic inflammatory diseases. The aim was to assess if these pathways are involved in curcumin-mediated effects on LPS-induced expression of these cytokines in macrophages. RAW 264.7 murine macrophages were stimulated with Escherichia coli LPS in the presence and absence of non-cytotoxic concentrations of curcumin. Curcumin potently inhibited LPS-induced expression of IL-6, TNF-alpha and COX-2 mRNA and prevented LPS-induced inhibition of SOCS-1 and -3 expression and the inhibition of the activation of p38 MAPKinase by modulation of its nuclear translocation. In conclusion, curcumin potently inhibits expression of LPS-induced inflammatory cytokines in macrophages via mechanisms that involve modulation of expression and activity of SOCS-1 and SOCS-3 and of p38 MAPK. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Curcumin; Innate immunity; Cell signalling; Cytokines; NF-kappa B; MAPK; SOCS